Automated diagnosis of brain tumor classification and segmentation of magnetic resonance imaging images - B. Muddaraju, Chandrakala; Shrinivasa, Shrinivasa; Narasimhamurthy, Shobha; Sontakke, Vaishali (IAES International Journal of Artificial Intelligence (IJ-AI), 2024)
Brain tumors are one of the most prevalent disorders of the central nervous system and are dangerous. For patients to receive the best treatment, early diagnosis is crucial. For radiologists to correctly detect brain tumor images, an automated approach is required. The identification procedure can be time-consuming and prone to mistakes. In this work, the issue of fully automated brain tumor classification and segmentation of magnetic resonance imaging (MRI) including meningioma, glioma, pituitary, and no tumor is taken into consideration. In this study, convolutional neural network (CNN) and mask region-based convolutional neural network (R-CNN) are proposed for classification and segmentation problems respectively. This study employed 3,200 images as a training set and the system achieved an accuracy of 96% for classifying the tumors and 94% accuracy in segmentation of tumors.